Consumer Dispute Settlement: A Comparative Study on Indonesian and Malaysian Law - Norma Sari (Future Science)
Consumer dispute settlement becomes an important instrument for protecting consumers. This study aims to analyze (i) the urgency of consumer dispute settlement body and small claim mechanism; (ii) the comparison of consumer dispute settlement law in Indonesia and Malaysia; (iii) a lesson from Malaysia concerning small claim court. This research was conducted as a library research. The results show that urgency of consumer dispute settlement body and small claim mechanism are to guarantee ultimate consumer interest. Comparing of consumer dispute settlement law in Indonesia and Malaysia, each institution and mechanism having advantages and disadvantages to consider for betterment in the future. Consumer Dispute Agency is a middle way or a combination off SCC system and specific dispute resolution body. But, Indonesia needs to reiterate the existing Consumer Protection Act regarding the duty and authority of Consumer Dispute Settlement Agency. There is authority overlap with other agencies needed to be addressed.